2018
DOI: 10.1029/2017jc013666
|View full text |Cite
|
Sign up to set email alerts
|

Malvinas Current at 40°S–41°S: First Assessment of Temperature and Salinity Temporal Variability

Abstract: The temporal variability of 11 months of in situ velocity, temperature, and salinity data collected at five moorings deployed at 40°S–41°S across the shelf‐break in the Southwestern Atlantic is analyzed. Two distinct regimes characterized by strong and weak along‐slope velocities are present. During the strong regime the Malvinas Current flows northward through the moorings while during the nearly 5 months long weak regime reversals of the along‐slope velocities are frequently observed. Comparison with the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…A synoptic situation during the last MC mooring period, a year we carefully studied (Artana, Ferrari, Koenig, et al, 2018;Ferrari et al, 2017;Paniagua et al, 2018) illustrates the model performance in this region. The model reproduces the rich mesoscale activity from the Confluence region showing filaments and small eddies as those observed in high resolution satellite imagery (Barré et al, 2006).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synoptic situation during the last MC mooring period, a year we carefully studied (Artana, Ferrari, Koenig, et al, 2018;Ferrari et al, 2017;Paniagua et al, 2018) illustrates the model performance in this region. The model reproduces the rich mesoscale activity from the Confluence region showing filaments and small eddies as those observed in high resolution satellite imagery (Barré et al, 2006).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In situ time series near the BMC are rather scarce. Current meter mooring data in the MC have been obtained at approximately 41°S along Jason2 track #26 (Figure 1d) near the Confluence with the BC at three different times: in 1993-1995 (Vivier & Provost, 1999a), 2001-2003(Spadone & Provost, 2009, and 2014-2015 (Paniagua et al, 2018). At 41°S, the MC has mainly a barotropic equivalent structure due to the weak stratification and the steep topography (Vivier & Provost, 1999a) and is made of one single core in contrast to the several narrow jets observed south of 42°S (Piola et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The latitude and longitude of these fronts changes continuously in time, at scales that vary from weeks to years. Several recent studies have identified the existence of two opposite regimes in the BMC—named weak and strong Malvinas flow—which are expressed in terms of the intensity of the along‐slope MC near 41°S (Artana et al, ; Ferrari et al, ; Paniagua et al, ). During the weak Malvinas regime, the SAF does not reach 41°S over the slope, the BCF overshoots as far as 44°S, and the eddy kinetic energy (calculated at time scales less than 20 days) increases; during the strong Malvinas regime, the SAF and BCF meet near 39°S along the slope, the BCO breaks down as an isolated anticyclone, and the eddy kinetic energy decreases.…”
Section: Introductionmentioning
confidence: 99%
“…We aim at describing the specific state at the time of the cruise, not only identifying the associated circulation patterns but also exploring what their complexity tells us about the frontal evolution and dominant processes. For this purpose, we combine high‐resolution hydrographic and velocity data in the upper 2,000 m, from a cruise carried out in March 2015, with velocity time series for the along‐slope MC at about 41°S (Ferrari et al, ; Saraceno et al, ; Paniagua et al, ) and remote‐sensing altimetry and temperature data over the entire region. The baroclinic and barotropic water mass transports are calculated using inverse models at two different spatial scales: frontal area and confluence region.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to sea surface studies, the subsurface variability of θ and S in the BMC remains barely explored. Paniagua et al (2018) have reported θ/S changes of 0.3°C/0.18 in 3 days at a slope mooring in the path of the MC (near 41°S and 1000 m depth). This high-frequency variability has been ascribed to either the intense mesoscale activity of the region, with eddies translating at velocities between 1 and 10 km/d (Mason et al, 2017;Pilo et al, 2015) or to the east-west and north-south BMC migrations at speeds up to 10 km/d (Garzoli & Bianchi, 1987;Legeckis & Gordon, 1982).…”
Section: 1029/2019gl084246mentioning
confidence: 99%